Revisiting the Green City Concept in the Tropical and Global South Cities Context: The Case of Indonesia - Zain, Alinda F. M.; Pribadi, Didit O.; Indraprahasta, Galuh S. (Frontiers in Environmental Science, 2022)
Urban areas play a key role in reaching global sustainability as they produce a high amount of waste and emissions, consume a lot of resources, and perform as the prime mover of the global economy. Unsustainable urbanization will generate multidimensional impacts on the earth’s socio-ecological system that is nearly impossible to be managed. As a preemptive action, urban sustainability has been considered as one of the most important targets in the Sustainable Development Goals. Within this context, the green city has emerged as a widely adopted concept around the globe. In the Global North, the concept of a green city has been incrementally developed as efforts to mainstream green infrastructure and nature-based solutions approaches in supporting ecosystem services. Quite the contrary, in the Global South cities, due to their rapid and vast urbanization process, the green city has been fragmentally adopted. Previous studies have proposed three factors, i.e., urbanization, biophysics, and governance, underlying the different approaches of green city development between cities in the Global North and South. Still, more studies are needed to explicate these factors and how these will in turn shape a particular green city trajectory in Global South cities. This study aims to respond to these questions based on green city experimentation in Indonesia. An exploratory study was done based on a literature review and participant observation. The results exhibit that the green city program in Indonesia largely focused on the development of green open spaces which has ultimately failed to improve the urban environment and sustainability. Incorporating local socio-ecological aspects coupled with integrated multi-level and multi-actors’ governance is recommended to increase the green city performances.